Immune-Escape Hepatitis B Virus Mutations Associated with Viral Reactivation upon Immunosuppression - Ivana Lazarevic; Ana Banko; Danijela Miljanovic; Maja Cupic (Viruses, 2019)
Hepatitis B virus (HBV) reactivation occurs as a major complication of immunosuppressive therapy among persons who have recovered from acute hepatitis and those who have controlled chronic infection. Recent literature data emphasize the presence of a high degree of S gene variability in HBV isolates from patients who developed reactivation. In reactivated HBV, the most frequently detected mutations belong to the second loop of “a” determinant in HBsAg. These mutations were identified to be immune escape and responsible for vaccine- and diagnostic-escape phenomena. Their emergence clearly provides survival in the presence of a developed humoral immune response and is often associated with impaired serological diagnosis of HBV reactivation. The knowledge of their existence and roles can elucidate the process of reactivation and strongly highlights the importance of HBV DNA detection in monitoring all patients with a history of HBV infection who are undergoing immunosuppression. This review discusses the possible influence of the most frequently found immune-escape mutations on HBV reactivation.